AB0819-HPR Is the rhematic patient ready to accept a more specialised health management offered by his nurse?. (23rd January 2014) - Vasile, D. M.; Ioan, C.; Berghea, F.; Iacob, M.; Predeteanu, D.; Canea, F.; Ghidu, E. A.; Secrier, M.; Neatu, S.; Ionescu, R.
Abstract : Background: The role of the rheumatology nurse varies from country to country but what all countries have in common is the ascendant trend of nurse's responsibilities in the rheumatology ward. Usually nurses are involved in patient education and monitoring of DMARDs, biologic treatments and other drug regimes. In some countries patients are regularly followed up in nurse-run clinics and in these your joints may be examined, blood test monitoring will be checked, drug doses may be changed or a joint injection undertaken to optimize the control of the arthritis. Is not unusual (in some hospitals) for a nurse to be involved in scientific research or to prescribe medications. We have to accept that many of these activities were not done by nurses in the past; in addition, the society is changing – medical information is widely available and patients demand more from their doctors (at least more than a patient could discover on the internet). But is this transfer of responsibilities from doctors to nurses acceptable for a more educated patient? Objectives: To evaluate what patients expect from a rheumatology nurse and what they are ready to accept as service provided by rheumatology nurses in the future. Methods: In a focus group exercise we identified the main tasks associated in present with a rheumatology nurse in a specialized hospital. In a literature review we identified additional tasks a rheumatology nurse has to fulfill in various European and US settings. A Survey-Monkey questionnaire was developed to evaluate patients' opinion regarding each of these tasks; patients from 8 rheumatology wards answered on a Likert scale (from 1 to 10). Data was analyzed by using SPSS 16.0 software package. Results: A number of 40 patients answered the questions (35% males and 65% females). Age (mean (SD)) was: 45.75 (14.72) years. The top 5 tasks mostly associated with a rheumatology nurse in present include: to manage various injectable procedures - 9.8 (0.4), to help doctors in minima invasive procedures – 9.05 (1.5), to know what to do in pain management – 8.8 (2.1), to recognize signs and symptoms of a flare – 8.2 (2.64). The 3 last positions in this rank are: to act as a musculoskeletal ultrasound technician – 5.5 (3.2), to perform home visits -6.2 (3.7), to educate patient – 6.9 (2.7). Regarding the future role of a rheumatology specialized nurse our responders indicated their interest in the following tasks: to recognize and react to the first signs of a drug adverse reaction – 9.6 (0.5), to be involved in the evaluation of socio-economic impact of the disease on the patient and his family -8.2 (2.7) but they do not see a role for nurses in ultrasonography -2.2 (2.6) and in evidence based medicine (as literature reviewer) -1.8 (1.3). Conclusions: Although the medical environment is changing our patients seem to be a little bit behind of the world-wide trend. Some energic actions have to be initiated in order to educate our patients in this field, too. Otherwise we may face the increasing dissatisfaction of patients that consider them not being treated with enough care and competence. Disclosure of Interest: None Declared